Analisis Motivasi Wisatawan Berkunjung ke Destinasi Wisata Alam Air Terjun Proklamator Kabupaten Tanah Datar - Sabar Menanti (Journal of Tourism Sciences, Technology and Industry, 2026)
Nature-based tourism continues to grow and plays an important role in enhancing regional appeal. Proklamator Waterfall in Tanah Datar Regency is a natural destination experiencing rising visitor numbers, yet the factors driving tourists' motivation to visit remain underexplored. This study aims to analyze the internal and external factors influencing tourists' motivation to visit Proklamator Waterfall and to identify the most dominant factor, applying the tourism motivation theory of Crompton for internal factors and Uysal and Jurowski for external factors. A quantitative descriptive approach was applied to 150 respondents determined through the Cochran formula with accidental sampling. Data were collected via a five-point Likert questionnaire, validated using Pearson Product Moment and tested for reliability with Cronbach's Alpha, then analyzed descriptively using frequency, percentage, mean, and Respondent Achievement Level. Results show internal factors obtained a mean of 4.0967 (high category) and external factors 4.0633 (high category). The exploration and evaluation of self indicator was most dominant for internal factors (mean 4.41), while outdoor/nature was most dominant for external factors (mean 4.24). Findings indicate that tourists' motivation to visit Proklamator Waterfall is more strongly driven by internal factors, while external factors reinforce their visiting decisions through the destination's natural appeal.